2017
DOI: 10.5114/wiitm.2017.67677
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of aortic rupture after deployment of a bare stent in the treatment of aortic dissection in a patient with giant-cell arteritis.

Abstract: Giant-cell arteritis is associated with a higher risk of aortic aneurysm and aortic dissection formation. We present a women with aortic dissection type B treated with a stent graft and bare-metal stent implantation. After the stent deployment we noticed aortic rupture, which was successfully treated with implantation of an additional stent graft. This report highlights the difficulty of endovascular therapy in patients with giant-cell arteritis. We have to bear in mind that chronic inflammation of the aorta l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We try to avoid uncontrollable rupture of the intima in the visceral region (covered only by an aortic BMS), due to the fact that complete re-lamination is sometimes impossible in this region, no matter how hard it is forced. 12,26 Instead of STABILIZE (proposed by Mellisano 26 ), we prefer to reinforce the aortic BMS by a simple modification (proposed by He 8 ). In this technique, the thoracic stent-graft is deployed inside the distal BMS-XL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We try to avoid uncontrollable rupture of the intima in the visceral region (covered only by an aortic BMS), due to the fact that complete re-lamination is sometimes impossible in this region, no matter how hard it is forced. 12,26 Instead of STABILIZE (proposed by Mellisano 26 ), we prefer to reinforce the aortic BMS by a simple modification (proposed by He 8 ). In this technique, the thoracic stent-graft is deployed inside the distal BMS-XL.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the potential risk of aortic rupture, and lack of information concerning follow up the STABILIZE technique was not widely accepted. 12 In order to improve the remodeling rate and reduce the frequency of late interventions, we introduced the E-PETTICOAT technique. 13,14 This is based on an extension of the standard Petticoat technique by the placement of 2 covered stents within the abdominal BMS as parallel iliac stent grafts, starting just below the renal artery and terminating below the distal tear, including down to the iliac bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Other complications of TAAs secondary to GCA include ischemic stroke, upper extremity stenosis, and death. 15 , 16 In a rare case, Rynio et al 17 reported that secondary to the inflammatory process within the aortic wall, the integrity of the wall is compromised leading to increased fragility as compared with noninflammed aortic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…This was done as a preparation of the landing zone for further procedures in the thoracic and thoracic-abdominal aorta in the future. A Tri-lobe balloon (Gore, Flagstaff, Arizona, 86003-2400 USA) was used to expand the stent grafts and their connections over the entire length, except for the last segment of the distal stent, to avoid aortic rupture or stent-induced new entry (SINE) [ 3 ]. Afterwards the guide was removed from the ventricle and valve.…”
Section: Methodsmentioning
confidence: 99%